2019
DOI: 10.1016/j.cgh.2018.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Does Not Reduce Liver Fat Scores in Patients Receiving Antiretroviral Therapy for HIV Infection

Abstract: In a secondary analysis of data from a trial of patients receiving treatment for HIV infection, hepatic steatosis increased over time, regardless of statin treatment, and was independently associated with markers of immune activation. Patients who received rosuvastatin appeared to have a nonsignificant increase in hepatic steatosis over 96 weeks. Despite their ability to reduce the risk of cardiovascular disease, statins do not appear to reduce hepatic steatosis. Clinicaltrials.gov no: NCT01218802.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Despite effective viral suppression with ART, gut damage is not reversed 3,4 . Much of the current research effort is looking at therapeutic strategies to restore gut structural integrity, in the hope of reducing non-AIDS related comorbidities 1,5 . The underlying mechanisms of gut structural damage are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Despite effective viral suppression with ART, gut damage is not reversed 3,4 . Much of the current research effort is looking at therapeutic strategies to restore gut structural integrity, in the hope of reducing non-AIDS related comorbidities 1,5 . The underlying mechanisms of gut structural damage are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Another trial showed that 24 weeks of vitamin E treatment decreased ALT and the degree of hepatic steatosis in HIV mono‐infected patients with non‐alcoholic steatohepatitis and showed no change in triglycerides, total cholesterol, HDL cholesterol, and HOMA‐IR 20 . Nevertheless, a randomized controlled trial of statin versus placebo, 147 HIV‐infected individuals with 96‐week follow‐up had hepatic steatosis increased over time, regardless of statin treatment 21 . Future clinical trials would take into consideration disease heterogeneity and target patients with specific characteristics, such as sex, hormonal status, genetic predisposition, metabolic and microbiota signatures, and the presence or absence of comorbid conditions 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive search for the literature from these databases yielded 795 records that were screened and evaluated at the title, abstract and keywords level (Figure 1). Finally, 20 studies [12][13][14]16,[19][20][21][22][23][41][42][43][44][45][46][47][48][49][50][51][52] were included, of which 12 trials used rosuvastatin of either 10, 20 or 80 mg, four used atorvastatin of 10, 30 and 40 mg, four used pravastatin at 40 mg and one used pitavastatin of 2 mg. These studies were published in peer-reviewed journals between 2004 and 2021, thus tracing old and advanced evidence on statins in PLHIV taking ART.…”
Section: Search General Characteristics and Quality Of Included Trialsmentioning
confidence: 99%
“…This problem has prompted other researchers to conduct clinical trials investigating this paradigm. Surprisingly, researchers have reported contradicting findings, with some showing consistently improved HIV surrogate markers [11][12][13][14][15][16][17][18] and others showing negative findings [19][20][21][22][23]. HIV as a chronic infection is closely associated with inflammation due to the continuously rising viral load [24,25].…”
Section: Introductionmentioning
confidence: 99%